Analisis Metode GPS Kinematik Menggunakan Perangkat Lunak RTKLIB - Henri Kuncoro; Irwan Meilano; Dina Anggraeni Sarsito (Indonesian Journal of Geospatial, 2013)
Abstract. One of the GPS kinematic processing software that developed in the current is RTKLIB. RTKLIB is the software which people can downloaded free and used free for it. This software can also perform data processing in fast and the data processing can be integrated in post-processing and real-time. In this study, the ability of RTKLIB tested by using GPS observation data with variations of the baseline length when earthquake not occured and earthquake offset detection from the GPS baseline processing results during earthquake. In this testing the stability of the GPS data processing results are ascertainable and it can be seen also the ability and reliability of the software in detecting earthquake offset. For comparison of the data processing results quality with RTKLIB, in this study selected TTC (Trimble Total Control) to process the GPS baseline of the same observasions From the results of GPS baseline processing with RTKLIB and TTC, it seems that RTKLIB results have better stability than TTC. In short baseline category have standard deviation less than 1 cm, in medium baseline category have standard deviation between 3-6 cm, whereas in long baseline category have standard deviation 3-8 cm. On the offset detection of earthquake, RTKLIB have ability to detect offset in more of baseline length variations than the TTC. Kata Kunci: GPS Kinematik, Offset Gempa, RTKLIBAbstract. One of the GPS kinematic processing software that developed in the current is RTKLIB. RTKLIB is the software which people can downloaded free and used free for it. This software can also perform data processing in fast and the data processing can be integrated in post-processing and real-time. In this study, the ability of RTKLIB tested by using GPS observation data with variations of the baseline length when earthquake not occured and earthquake offset detection from the GPS baseline processing results during earthquake. In this testing the stability of the GPS data processing results are ascertainable and it can be seen also the ability and reliability of the software in detecting earthquake offset. For comparison of the data processing results quality with RTKLIB, in this study selected TTC (Trimble Total Control) to process the GPS baseline of the same observasions From the results of GPS baseline processing with RTKLIB and TTC, it seems that RTKLIB results have better stability than TTC. In short baseline category have standard deviation less than 1 cm, in medium baseline category have standard deviation between 3-6 cm, whereas in long baseline category have standard deviation 3-8 cm. On the offset detection of earthquake, RTKLIB have ability to detect offset in more of baseline length variations than the TTC. Kata Kunci: GPS Kinematik, Offset Gempa, RTKLIB